A Few Facts About Your Journal - Nko’o Amvene, Samuel (HEALTH RESEARCH IN AFRICA, 2025)
Health Research in Africa (HRA) is an open source, monthly scholarly, multidisciplinary, peer reviewed medical journal that is partnered to Health Sciences and Disease, the official publication of the Faculty of Medicine and Biomedical Sciences (FMBS) of the University of Yaoundé I. Numerous basic health data from many African countries are still lacking in the medical literature and HRA seeks to fill this gap. Therefore, HRA covers all aspects of medicine, pharmacy, biomedical and health sciences, including health technologies, public health and societal issues. However, HRA values mostly pertinent applied research articles with impact on clinical care or public health. HRA is an “online first” publication, which means that all the publications articles appear on the website before being included in the print journal. The papers are published in full on the website, with open access. Acceptance of manuscripts by the editorial team is based on the originality, the quality of the work and validity of the evidence, the clarity of presentation, and the relevance to our readership. Publications are expected to be concise, well organized and clearly written. Authors submit a manuscript with the understanding that the manuscript (or its essential substance) has not been published other than as an abstract in any language or format and is not currently submitted elsewhere for print or electronic publication. HRA’s publication and ethics Policies follow the recommendations of the International Committee of Medical Journal Editors (ICMJE), the World Association of Medical Editors (WAME), the Council of Science Editors (CSE) and the Committee on Publication Ethics (COPE). HRA is published by Afrimvoe Medical Services, Yaounde (Cameroon). HRA Open Access license agreement Articles published in HRA are Open Access and distributed under the terms of the Creative Commons Attribution 4.0 International (CC BY CC ND 4.0), which permits others to distribute, remix, adapt, build upon this work, provided the original work is properly cited, the use is non-commercial and if you remix, transform, or build upon the material, you may not distribute the modified material, and the authors retain the copyright and full publishing rights over publication. Full HRA Open Access license agreement is identical to the creativecommons.org/licenses License